2020
DOI: 10.1016/j.seppur.2019.116328
|View full text |Cite
|
Sign up to set email alerts
|

Rare earth co-doped ZnO photocatalysts: Solution combustion synthesis and environmental applications

Abstract: A novel europium (Eu) and terbium (Tb) co-doped ZnO nanoparticles had been synthesized by a facile, cost efficient and rapid combustion method. The physical and chemical properties of the as-synthesized nanoparticles were determined by XRD, SEM, EDS, BET, FTIR, XPS, UV-vis DRS, PL, EIS and photocurrent density. XRD patterns confirm that Eu and Tb ions are stably inserted into the framework of ZnO, and the crystallite size decreases to 21 nm compared to that of pure ZnO (32 nm) as the amount of co-dopants incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(48 citation statements)
references
References 60 publications
4
44
0
Order By: Relevance
“…In the case of Tb (III), the deconvolution is more difficult due to poorly resolved signals. More specifically, the analysis of the Tb 4 d 5/2 signal tends to indicate that two forms of Tb may coexist at ~149 eV and 152–151 eV; the REE may coexist as bound Tb (III) but also under its oxidized form, i.e., Tb (IV), respectively [ 68 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the case of Tb (III), the deconvolution is more difficult due to poorly resolved signals. More specifically, the analysis of the Tb 4 d 5/2 signal tends to indicate that two forms of Tb may coexist at ~149 eV and 152–151 eV; the REE may coexist as bound Tb (III) but also under its oxidized form, i.e., Tb (IV), respectively [ 68 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, the doping of rare-earth elements can effectively regulate the electronic and geometric structures of electrocatalysts, thus improving their electrical conductivity and internal catalytic activity. [22]. However, there still are few reports about enhancing the intrinsic OER activity of MOFs by rare-earth element doping, especially under large currents [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al reported that Ni–Fe–Ce–LDH microcapsules exhibited a high OER activity owing to the optimized electronic structure of 3D LDHs through Ce species doping [ 21 ]. Ahmad et al found that doped Eu and Tb ions could enter the lattice of ZnO, and the resulting ZnO had a large specific surface area and high porosity [ 22 ]. However, there still are few reports about enhancing the intrinsic OER activity of MOFs by rare-earth element doping, especially under large currents [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…This method is essentially an exothermal redox reaction between fuels and oxidizers. 18 20 In general, the oxidizers are metal nitrates and the fuels are glycine, citric acid, urea, etc. 21 Additionally, the energy generated by exothermal reactions can be used to sustain the reaction system.…”
Section: Introductionmentioning
confidence: 99%